China-Africa economic relation: a double-edged sword for Africa. (18th April 2020) - Kalu, Kenneth; Aniche, Ernest Toochi
China-Africa economic relation has expanded significantly since the 1990s. In recent years, China's activities in African countries have attracted criticisms bothering on fears that financial flows from China could exacerbate poor governance and human rights abuses in these countries. However, our assessment of the dynamics of China's engagements with Africa shows that the biggest potential negative impact of these engagements is not necessarily on governance and human rights, as portrayed by Western politicians and commentators, but largely on economic factors. Specifically, China's activities in Africa could delay the emergence of a vibrant manufacturing sector in Africa, if African countries continue to import cheap manufactured products from China while relying on the export of minerals as the mainstay of their economies. Consequently, this paper recommends that African countries should focus on directing China's investment in the continent strategically towards stimulating domestic manufacturing in the respective countries.